2014
DOI: 10.2319/043014-312.1
|View full text |Cite
|
Sign up to set email alerts
|

Lateral comparisons using Fishman's skeletal maturation assessment

Abstract: Objective: To assess lateral differences between ossification events and stages of bone development in the hands and wrists utilizing Fishman's skeletal maturation indicators (SMIs). Materials and Methods: The skeletal ages of 125 subjects, aged 8 to 20 years, were determined with left and right hand-wrist radiographs using Fishman's SMI assessment. Each subject was also given the Edinburgh Handedness Questionnaire to assess handedness. The skeletal ages of both hand-wrist radiographs were analyzed against eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…The most obvious difference occurred in the radius with the right exceeding left in 57% children. But, more studies 6,8,14 on radiographic bone age revealed no inter‐side differences. This may due to the precision error of the evaluation method used in their studies 14 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The most obvious difference occurred in the radius with the right exceeding left in 57% children. But, more studies 6,8,14 on radiographic bone age revealed no inter‐side differences. This may due to the precision error of the evaluation method used in their studies 14 .…”
Section: Discussionmentioning
confidence: 93%
“…What is more, the differences between left and right bones of hand and wrist were proved to be insignificant when it comes to evaluating bone age as a whole 3,4 . But, lateral asymmetry did exist if the bones were compared one by one 4–8 …”
mentioning
confidence: 92%
See 1 more Smart Citation
“…En ortodoncia y ortopedia maxilar, es muy importante valorar el momento en el que se producen los cambios, tanto biológicos como estructurales, con relación al crecimiento y desarrollo de los maxilares, para identificar el inicio del crecimiento puberal y así fundamentar el tratamiento y corrección de las diferentes alteraciones tanto dentarias como esqueléticas ( 1-4 ), a fin de obtener un resultado positivo en el momento de la planificación y permitir que los diversos tipos de dispositivos funcionales corrijan las discrepancias o alteraciones que se puedan presentar ( 5,6 ). Para obtener la efectividad o una respuesta positiva en cuanto a la aplicación adecuada de los aparatos funcionales, es importante conocer y evaluar en gran medida la maduración esquelética y su potencial de crecimiento de forma individual en cada individuo, para así contar con información importante y anticiparnos a los resultados que nos proponemos en el tratamiento ( [7][8][9] ). Se debe de tener en cuenta que el porcentaje del crecimiento tanto de las estructuras esqueléticas como de las dentarias no es constante en el desarrollo ( 9, 10 ).…”
Section: Introductionunclassified
“…La valoración de la maduración de las vértebras cervicales ha demostrado ser un método que presenta una alta y recíproca relación con el análisis de maduración ósea mano-muñeca ( [21][22][23][24] ). Por tanto, en este estudio se utilizan las radiografías laterales de cabeza que se solicitan en ortodoncia y se evita así el uso de radiografías adicionales y, lo más importante, la exposición adicional del paciente a la radiación ( [25][26][27][28][29] ).…”
Section: Introductionunclassified